1. 8c^2-26c+15= (4c-3) (2c-5). Break the expression into groups: =(8c^2-6c)+(-20c+15). Factor out 8c^2-6c: 2c(4c-3). Factor out -5 from -20c+ 15: -5(4c-3). Lastly factor out common term (4c-3) and thats how you'll get your answer (4c-3) (2c-5).
2. common factors for 270 and 360 is 90.To find this write the factors of each and find the largest one.270: 1, 270, 2, 135, 3, 90, 5, 54, 6, 45, 9, 30, 10, 27, 15, 18360: 1, 360, 2, 180, 3, 120, 4, 90, 5, 72, 6, 60, 8, 45, 9, 40, 10, 36, 12, 30, 15, 24, 18, 20
3. The factors for 8 a3b2 and 12 ab4 is 4. because 8: 1, 2, 4, 812: 1, 2, 3, 4, 6, 12.
4. 81a^2+36a+4= (9a+2)^2. Break down the expression into groups: (81a^2+18a)+(18a+4). Factor out 9a from 81a^2 +18a: 9a(9a+2). Factor out 2 from 18a+4: 2(9a+2). so the groups you got are now 9a(9a+2)+2(9a+2). Lastley factor out common term (9a+2) to get (9a+2) (9a+2). Finally you get the answer (9a+2)^2.
5. mn-15+3m-5n= (n+3)(m-5). factor out m from nm+3m: m(n+3). Factor out -5 from -5n-15: -5(n+3). And thats how you get the number (n+3)(m-5)
Hope this helped :) Have a great day
Hold on i believe its C but let me go look on google and i'll get back to you to sure
Exchange rate refers value of a currency in another.The cost of the decorative mug is 83.98 China Yuan.
<h3>What is the exchange rate?</h3>
The term exchange rate has to do with the value of a currency in another currency. Given the fact that international trade is the mainstay of the global economy, it is important that one currency should be converted to another for the purpose of the ease of doing business.
The dollar is often the international currency for trade. Its us always necessary to convert the dollar into the local currency of the country where the business is done using the correct exchange rate.
Now If I want to convert the cost of the decorative mug to China Yuan;
I already know that;
1 US dollar = 6.4651 China Yuan
12.99 US dollar = 12.99 US dollar * 6.4651 China Yuan/1 US dollar
= 83.98 China Yuan
Hence, the cost of the decorative mug is 83.98 China Yuan.
Learn more about exchange rate:brainly.com/question/22996931
#SPJ1
Answer:
C and D
Step-by-step explanation:
Equating the line A and the parabola, we get
-3x + 2 = x² - 3x + 4
0 = x² - 3x + 4 +3x - 2
0 = x² + 2
-2 = x²
which has no real solutions. Then, the line A and the parabola don't intersect each other.
Equating the line B and the parabola, we get
-3x + 3 = x² - 3x + 4
0 = x² - 3x + 4 + 3x - 3
0 = x² + 1
-1 = x²
which has no real solutions. Then, the line B and the parabola don't intersect each other.
Equating the line C and the parabola, we get
-3x + 5 = x² - 3x + 4
0 = x² - 3x + 4 + 3x - 5
0 = x² - 1
1 = x²
√1 = x
which has 2 solutions, x = 1 and x = -1. Then, the line C and the parabola intersect each other.
Equating the line D and the parabola, we get
-3x + 6 = x² - 3x + 4
0 = x² - 3x + 4 + 3x - 6
0 = x² - 2
2 = x²
√2 = x
which has 2 solutions, x ≈ 1.41 and x ≈ -1.41. Then, the line D and the parabola intersect each other.